TAKHRIJ AL-FURU’ ALAL USUL PERIODE IJTIHAD DI MASA SHAHABAT DAN TABI’IN (Kajian Sosiologi - Antropologi Hukum Islam) - Erwan, Erwan (IAIN Batusangkar, 2018)
This research reveals the truth about the reality of Islamic law and its scope. This study was a library research. The data were obtained through the library method, namely by collecting data and materials from books that are relevant to this discussion, by reading, studying, and analyzing all the sources. Sociological-anthropological understanding means discussing the truth of a fact in depth. Law as something that is related to humans, then the relationship between humans and other human beings is in a life interaction. Because without the interaction of life there will be no law (ibi societas ibi ius, zoon politicon). Law serves to regulate relations between people. But not all human actions have their regulation. Only actions or behavior that are classified as legal actions. Legal law relations consist of bonds between individuals and individuals and between individuals and communities. In its efforts to regulate, the law adapts to the interests of society well. As a collection of rules or principles, the law has a general and normative content, the legal principle aims to protect the interests of human beings as social beings. Therefore the law must be obeyed, must be carried out and maintained, but not violated. Humans are given the mind to think, then ijtihad is the deployment of the ability of the brain. The real fact shows that thisdynamics had existed during the Prophet's benediction and tabi'in.